Third sector economy literature: A bibliometric review and content analysis: Third sector economy literature mapping (IIUC Business Review, 2026)
The third sector economy comprises nonprofit, voluntary, and social organizations of an economy that mostly remain out of mainstream economics research. The present study is the first-ever attempt to review the third-sector economy literature, primarily using a quantitative bibliometric approach. Along with the brief content analysis, the study used historical analysis, illustration of keywords co-occurrence network, thematic map and three-field plot sketching and, importantly, analyses of the most contributing sources, countries, and authors. The results of the analyses reveal that the mainstream studies on third sector economy come from various social sciences other than economics. The micro and macroeconomic aspects of the third sector economy are yet to be explored rigorously, although both keyword and thematic analyses indicate that some studies incorporated the ‘social economy’ as a sub-stream. Based on the study's findings, some future research scopes have been put forward that may contribute to academics.IIUC Business Review, Vol.-12, Issue-1, December 2023, pp. 87-118